Lloyd's open form 1980 and 1990: born of necessity, has it succeeded? - Shadel, Tendresse N'Deyh (Institute of Marine and Environmental Law, 2023)
In earlier shipping days, salvage services were often provided to vessels and maritime properties in danger at sea by individual acts. This was done without salvage contract between the parties. The recent availability of instantaneous means of communication and especially motor driven vessels has resulted in services in the nature of salvage having come to be governed frequently by an agreement in which both the provider and the recipient have been held to owe duties to each other. A factor contributing to this development was the introduction of· Standard Forms of Salvage Agreements. These provided for quantification of the salvor's remuneration by arbitration if it could not be agreed upon by the parties.